Economic origins of dictatorship and democracy - Acemoglu, Daron; Robinson, James A., 1960- (Cambridge University Press, 2006)
This book is the first to use modern social science methodology systematically to explain why some countries are democracies while others are not. Why does democracy sometimes persist and consolidate while other times it collapses? The treatment shows that whether or not a society becomes democratic depends on several factors.
Keywords: Democracy -- Economic aspects.; Democratization.; Equality.; Political culture.; Dictatorship.; Comparative government.; Démocratie -- Aspect économique.; Démocratisation.; Inégalité sociale.; Culture politique.; Dictature.; Institutions politiques comparées.; dictatorships.; comparative politics.; POLITICAL SCIENCE -- Political Ideologies -- Democracy.; Démocratie.; Aspects économiques.; Comportement politique.; Analyse comparative.; Modèles économiques.; Comparative government; Democracy -- Economic aspects; Democratization; Dictatorship; Equality; Political culture; Demokratie; Entstehung; Diktatur; Wirtschaftssystem; Ökonomische Theorie der Demokratie; Ökonomische Theorie der Politik; Democracy; Economic conditions; Dictatorships; Economic models; International comparisons; Overseas item; Electronic book.; Electronic books.